Risk of subsequent disabling or fatal stroke in patients with transient ischaemic attack or minor ischaemic stroke: an international, prospective cohort study. Issue 10 (October 2022) - Hobeanu, Cristina; Lavallée, Philippa C; Charles, Hugo; Labreuche, Julien; Albers, Gregory W; Caplan, Louis R; Donnan, Geoffrey A; Ferro, Jose M; Hennerici, Michael G; Molina, Carlos A; Rothwell, Peter M; Steg, Philippe Gabriel; et al.
Summary: Background: Patients who have had a transient ischaemic attack or minor stroke have an increased risk of cardiovascular events for the following 5 years. We aimed to assess 5-year functional outcomes in patients with transient ischaemic attack or minor ischaemic stroke and to determine the factors associated with long-term disability. Methods: We analysed data from patients in TIAregistry.org, an international, prospective, observational registry of patients with transient ischaemic attack or minor ischaemic stroke from 61 specialised centres in 21 countries. Patients aged 18 years or older who had a transient ischaemic attack or minor stroke within the previous 7 days between May 30, 2009, and Dec 30, 2011, with a baseline modified Rankin scale (mRS) score of 0–1, and who had been followed up for 5 years, were eligible for inclusion in this study. We evaluated whether existing comorbidities and stroke recurrence, categorised as disabling (mRS score of >1, including death) or non-disabling (mRS score of 0–1), at 5 years after baseline, were associated with poor functional outcome (defined as an mRS score of >1). We used multivariable generalised equation models for factors associated with poor functional outcome at 5 years and multivariable cause-specific Cox hazard regression models in case of stroke recurrence. Findings: Between May 30, 2009, and Dec 30, 2011, 3847 eligible patients were included in the study, 3105 (80·7%) of whom had an mRS evaluation at 5 years of follow-up. Median follow-up duration was 5·00 years (IQR 4·78–5·00). 710 (22·9%) of 3105 patients had an mRS score greater than 1 at 5 years. Factors associated with poor functional outcome at 5 years were older age (per 10-year increase, odds ratio [OR] 2·18, 95% CI 1·93–2·46; p<0·0001), diabetes of any type (1·45, 1·18–1·78; p=0·0001), history of stroke or transient ischaemic attack before the qualifying event (1·74, 1·37–2·22; p<0·0001), hypertension (1·38, 1·00–1·92; p=0·050), atrial fibrillation or flutter (1·52, 1·04–1·94; p=0·030), congestive heart failure (1·73, 1·22–2·46; p=0·0024), valvular disease (2·47, 1·70–3·58; p<0·0001), stroke as qualifying event (1·31, 1·09–1·57; p=0·0037), history of peripheral artery disease (1·98, 1·28–3·07; p=0·0023), history of coronary artery disease (1·32, 1·00–1·74; p=0·049), intracranial haemorrhage during follow up (4·94, 1·91–12·78; p=0·0013), and living alone (1·32, 1·10–1·59; p=0·0031). Regular physical activity before the index event was associated with reduced risk of poor functional outcome (OR 0·52, 95% CI 0·42–0·66; p<0·0001). 345 recurrent strokes had occurred at 5 years of follow-up, 141 (40·9%) of which were disabling or fatal. Stroke recurrence increased the risk of having a disability at 5 years (OR 3·52, 95% CI 2·37–5·22; p<0·0001). Recurrent disabling or fatal strokes were independently associated with older age (per 10-year increase, hazard ratio [HR] 1·61, 95% CI 1·35–1·92; p<0·0001), diabetes of any type (2·23, 1·56–3·17; p<0·0001), National Institutes of Health Stroke Scale score of greater than 5 at discharge (5·11, 2·15–12·13; p=0·0013), history of coronary artery disease (1·76, 1·17–2·65; p=0·0063), history of stroke or transient ischaemic attack before the qualifying event (1·54, 1·03–2·29; p=0·035), congestive heart failure (1·86, 1·01–3·47; p=0·044), stroke as qualifying event (1·73, 1·22–2·45; p=0·0024), mRS score of greater than 1 at discharge (2·48, 1·27–4·87; p=0·0083), and intracranial haemorrhage during follow-up (17·15, 9·95–27·43; p<0·0001). Regular physical activity before the index event was associated with reduced risk of recurrent disabling stroke at 5 years (HR 0·56, 95% CI 0·31–0·99; p=0·046), and 5-year disability without recurrent stroke (0·61, 0·47–0·79; p=0·0001). Interpretation: We found a substantial burden of disability (mRS score of >1) at 5 years after transient ischaemic attack or minor ischemic stroke, and most predictors of this disability were modifiable risk factors. Patients who did regular physical exercise before the index event had a significantly reduced risk of disability at 5 years compared with patients who did no exercise. Funding: AstraZeneca, Sanofi, Bristol Myers Squibb, SOS Attaque Cérébrale Association.